DETERMINAN CITRA HARGA DAN DAMPAKNYA TERHADAP NIAT PEMBELIAN - Ubaidillah, Hasan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
Aim this study to examine the effect of price image on the intention to make a purchase in modern retail in the region Gedangan Sidoarjo. The population of this study is consumers who make purchases at five modern retail stores. The sampling technique using accidental sampling, analysis techniques with multiple regression analysis. The analysis showed that all independent variables price level perception, value for money, price processibility positive and significant effect on the intention of making a purchase and price perceptibility have no positive and significance effect onÂ intention of making a purchase.